Кульчицький С. Комунізм в Україні: перше десятиріччя (1919-1928) - Дмитрієнко, М. Ф.; Табачник, Д. В. (Український історичний журнал, 2025)
Кульчицький С. Комунізм в Україні: перше десятиріччя (1919-1928). — К., 1996. — 400 с.